Modern innovative concepts of the management of the foreign economic activities of the enterprise - Khomiuk, Nataliia (Луцьк: Вежа-Друк, 2023)
One of the types of activities of enterprises includes entering international markets to expand their business activities to a new level. Current conditions also emphasize the need for innovation, which is a key factor in the development of enterprises and contributes to increasing their competitiveness. The market economy establishes a different number of indicators that affect the country's foreign trade. One of the tasks of the state is to create favorable conditions for the implementation of foreign economic activity. In the conditions of globalization, those countries, regions, and business entities that successfully adapt to the modern realities of socio-economic interaction based on innovation gain a competitive advantage. In the era of digital transformation, their activities are not possible without the use of information and communication technologies that contribute to cooperation with other participants in the global economic space. They actively introduce innovations in their practical activities and can integrate with other participants in the world market constructively.
Keywords: foreign activities of enterprises; international markets; the mechanism for the activation of foreign economic activity; 339.97